The difference between squat jump and countermovement jump in 770 male and female participants from different sports - Kozinc, Z.; Žitnik, J.; Smajla, D.; Sarabon, N. (European Journal of Sport Science, 2022)
Traditionally, a larger difference between countermovement (CMJ) and squat jump (SJ) was seen as beneficial, as it reflects the ability to utilize the stretch-shortening cycle. However, strong arguments have been made that this might not always be the case, as larger differences between the jumps could also suggest higher muscle-tendon slack, or poor capability to take this slack up quickly. The purpose of this study was to explore SJ and CMJ, as well as the CMJ to SJ difference (CMJSJDiff) in 9 groups of young athletes. In total, 712 athletes from various disciplines (mean age range: 15.7-36.3 years) and 58 physical education students (mean age: 19.6 years) participated in the study. The major finding of this study was that the groups that showed better SJ and CMJ performance did not show the larger CMJSJDiff. For instance, SJ and CMJ heights were highest in short-distance runners and lowest in long-distance runners, while the largest and smallest CMJSJDiff was shown in physical education students and speed skaters, respectively. Male athletes had a higher CMJSJDiff than female athletes, but the difference was very small. While a larger CMJSJDiff has been traditionally associated viewed as positive, our results could indicate both superior ability to utilize the stretch-shortening cycle, as well as poor ability of rapid force development and excessive muscle slack. Further studies are needed to directly investigate the associations between CMJSJDiff and indicators of athletic performance.